AGRICULTURALRESOURCES ALLOCATION AND ENVIRONMENTAL SUSTAINABILITY - BIONDO, Alessio Emanuele; BONAVENTURA, Luigi (Journal of Environmental Management and Tourism; Vol 5 No 2 (2014): JEMT Volume V Issue 2(10) Winter 2014, 2016)
This paper shows the direct linkage existing between the environmental sustainability and the diffusion of organic agriculture. The reason is that the environmental impact of organic agriculture is different and somehow less polluting than industrial (let us say, traditional) one. Moreover, the former delivers also healthier food, according to part of the literature. Thus, seeking for sustainability, the policy-maker may find easier to influence the allocation of natural resources in favour of the organic cultivation as an instrument to care Nature. In order to claim this rationale, a model of resource allocation is presented and the golden rule derived. The paper finally shows that organic agriculture generates a global positive externality, which implicitly measures the relevance of the balancing intervention on resources allocation.
Keywords: sustainability; organic food; organic agriculture; externalities